Review article Amyotrophic lateral sclerosis – looking for pathogenesis and effective therapy - Naganska, Ewa; Matyja, Ewa (Folia Neuropathologica, 2011)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by loss of motor neurons in the spinal cord, brain stem and motor cortex which dramatically reduces life expectancy. ALS occurs either in familial or, more frequently, in sporadic forms. It finally results in death due to respiratory failure that occurs typically 2-5 years after the disease onset. Although the aetiology of ALS remains largely unclear, its heterogeneity suggests that a combination of various factors, including endogenous and/or environmental ones, may be implicated in progressive motor neuron stress that results in the activation of different cell death pathways. Interactions between genetic, environmental, and age-dependent risk factors have been hypothesized to trigger disease onset. Despite extensive neurobiological, molecular and genetic research, at the beginning of the 21 st century ALS still remains one of the most devastating neurodegenerative diseases because of the lack of effective therapeutic strategies. It is a challenge for the clinical and scientific community. Better understanding of the aetiology of amyotrophic lateral sclerosis is necessary to develop effective treatment of this progressive neurodegenerative disease. This review presents the current state of knowledge in ALS research.